Effect of Weathering on Cd Mobilization in Different Sedimentary Bedrock Soils - Yongqiang Ning; Minglong Yang; Chutong Liu; Jiazhong Huang; Tianyi Wang; Yong Pang; Quanheng Li (Land)
Cd (cadmium) has been categorized as a crucial food pollutant by the World Health Organization. Research regarding Cd pollution mainly centers on the source of anthropogenic pollution. Nevertheless, there is scarce knowledge concerning the natural weathering input of Cd, particularly that from sedimentary rocks as bedrocks. Herein, we endeavored to explore the contribution of various sedimentary rocks (Quaternary sediments, mudstone, limestone, sandstone, shale, greywacke, and marl) under similar weathering conditions to the input of Cd in agricultural soils. The concentrations of Cd in soils with different bedrocks are as follows: sandstone: 0.30 ± 0.03 mg/kg (SME) > Quaternary sediments: 0.30 ± 0.04 mg/kg (SME) > shale: 0.25 ± 0.04 mg/kg (SME) > greywacke: 0.24 ± 0.03 mg/kg (SME) > mudstone: 0.24 ± 0.01 mg/kg (SME) > marl: 0.22 ± 0.02 mg/kg (SME) > limestone: 0.21 ± 0.03 mg/kg (SME). The results of major element oxides (K2O, MgO, Na2O, Fe2O3, and CaO) imply that Cd in soil primarily stems from the weathering of bedrocks. However, random forest analysis reveals that the soil formation processes of greywacke, mudstone, and marl lead to the loss of Cd in the soil, while those of shale and limestone result in the input of Cd into the soil. This study emphasizes that the process of Cd import and loss in soil is closely related to the type of bedrock and the weathering process.